2013
DOI: 10.1093/mnras/stt2250
|View full text |Cite|
|
Sign up to set email alerts
|

On the physics of radio haloes in galaxy clusters: scaling relations and luminosity functions

Abstract: The underlying physics of giant and mini radio halos in galaxy clusters is still an open question. We find that mini halos (such as in Perseus and Ophiuchus) can be explained by radio-emitting electrons that are generated in hadronic cosmic ray (CR) interactions with protons of the intracluster medium. By contrast, the hadronic model either fails to explain the extended emission of giant radio halos (as in Coma at low frequencies) or would require a flat CR profile, which can be realized through outward stream… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(105 citation statements)
references
References 114 publications
(259 reference statements)
1
103
0
1
Order By: Relevance
“…In addition a number of authors have identified the very broad (flat) spatial profiles of giant radio halos as a potential challenge for a purely hadronic origin of these sources, because in some cases a large, or radially increasing, energy density of CRp and/or magnetic field is required to generate the observed radio emission from radially distant, low target-ICM density, regions. [255][256][257][258][259]274 Potential constraints on the thermal -non-thermal connection and on the physics of radio halos also come from possible trends between the local synchrotron spectral indices and ICM temperatures. 38 Still, these relationships are only hints at the full picture.…”
Section: Observational Milestones and Origin Of Giant Radio Halosmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition a number of authors have identified the very broad (flat) spatial profiles of giant radio halos as a potential challenge for a purely hadronic origin of these sources, because in some cases a large, or radially increasing, energy density of CRp and/or magnetic field is required to generate the observed radio emission from radially distant, low target-ICM density, regions. [255][256][257][258][259]274 Potential constraints on the thermal -non-thermal connection and on the physics of radio halos also come from possible trends between the local synchrotron spectral indices and ICM temperatures. 38 Still, these relationships are only hints at the full picture.…”
Section: Observational Milestones and Origin Of Giant Radio Halosmentioning
confidence: 99%
“…Consequently Mpc-scale radio emission should be generated at some level in "all" clusters with luminosities that should vary depending on the cluster dynamical histories (e.g., accretion shock histories) and/or magnetic properties (e.g., histories of magnetic flux injection and amplification). 23,36,239,273,274 In this respect future radio surveys with sensitivities to diffuse cluster-scale emission much better than current surveys, will provide unique and critical constraints to the role played by secondaries. For reference, Hybrid models, that assume radio halos to be generated by the (re)acceleration of secondary particles by turbulence in cluster mergers, 172,177 predict that secondaries generated in more relaxed systems produce radio emission with luminosity marginally smaller than current upper limits in Figure 12.…”
Section: Open Problems and Future Effortsmentioning
confidence: 99%
“…Mazzotta & Giacintucci 2008;Giacintucci et al 2014b) suggests that turbulence may be reaccelerating electrons to produce the mini-haloes (Mazzotta & Giacintucci 2008;ZuHone et al 2013;Giacintucci et al 2014a). In addition, the secondary electron models similar to those for radio haloes have also been suggested as explaining the mini-haloes that indeed trace the region where the number density of thermal targets in proton-proton collisions is higher (Pfrommer & Enßlin 2004;Keshet & Loeb 2010;Zandanel et al 2014). Based on the role of turbulent motions in the ICM and the transport of cosmic rays, a potential evolutionary connection between mini-haloes and radio haloes has also been suggested (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…Still, contrary to the case of nearby giant radio halos, these limits do not put significant tension on a secondary origin of mini-halos (Brunetti & Jones 2014). For example, Zandanel et al (2014) proposed that mini-halos are primarily of hadronic origin, while giant radio halos experience a transition from a central hadronic emission to a leptonic emission component in the external regions due to CRe reacceleration. In the hadronic model, under relatively quiescent conditions, the electron spectrum will reach a steady-state condition where the energy losses and the gains due to injection balance each other out (Sarazin 1999).…”
Section: Introductionmentioning
confidence: 99%